Research Technologies of Teaching in Higher Education: Applying Multidimensional Analytical Approaches to the Study of Hydronymy of Western Kazakhstan (Journal of Educational Sciences, 2026)
The relevance of the research is determined by the need to develop new research methods and technologies for teaching higher education in the field of didactics of teaching philological sciences, including linguistics In particular, the article considers a research methodology for teaching the use of modern interdisciplinary methods for analyzing the hydronyms of Kazakhstan based on the material of the Western region. Hydronyms act as important markers of the features of the natural landscape, cultural memory, and historical processes, but traditional descriptive and etymological approaches do not fully reveal their multilayered structure.Deeper interpretation requires combining cognitive, semantic, and geoinformation methods, which can be effectively integrated into the training of bachelor’s, master’s, and doctoral students.The purpose of this work is to generalize a research -based teaching methodology in linguistics by systematizing contemporary approaches to cognitive, semantic, and cartographic modeling of regional hydronymy. The article shows the potential of their integration within a single analytical model and the potential of research teaching methods. The possibilities of using cognitive analysis to reconstruct conceptual frames, semantic clustering, and to identify motivational groups in order to identify areal patterns and spatial structures are considered.It is emphasized that such studies should be grounded in materials from topographic maps, archival sources, published works, and field data.The study illustrates that combining cognitive models with GIS visualization makes it possible to uncover hidden relationships between hydronyms and landscape characteristics, while semantic methods differentiate Turkic, Iranian, and other motivational layers. Spatial modeling confirms the key role of river systems in shaping the region’s toponymy. The scientific novelty of the work lies in substantiating a research-based learning technology built on the integration of cognitive, semantic, and cartographic approaches for multidimensional analysis of the target units. The results can be used in courses for training learners at different levels and more broadly in linguistics, geography, and cultural studies, as well as in developing regional cartographic resources, systematizing toponymic data, and research aimed at preserving linguistic heritage.Keywords: hydronymy, Western Kazakhstan, cognitive analysis, toponymic motivation, modern educational technologies.